Expiration Training Maneuver for Chronic Obstructive Pulmonary Disease with Congestive Heart Failure Grade II: A Case Report - Nury Nusdwinuringtyas; Siti Chandra Widjanantie (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) was characteristic by the inflammatory process in the airway which causes air trapping and hyperinflation, then followed by decreasing the respiratory muscle strength. Breathing training using the positive expiratory pressure (PEP) increasing respiratory muscle strength.Methods: A case presentation of a male, age was 60 years old diagnosed as COPD by The Global Initiative for Chronic Obstructive Lung Disease (GOLD) grade 4 group D, and Chronic Heart Failure (CHF) grade II, with complication of excessive phlegm, underweight, and weakness of respiratory muscle, have PEP for 8 weeks.Results: Spirometry evaluation before and after eight week of PEP have found; FEV1 22.12 and 22.42%, FVC 34.24 and 56%, FEV1/FVC 76.8 and 64%. Respiratory muscle strength before and after PEP showed the Muscle Inspiratory Pressure (MIP) 46 and 71 cmH2O, Muscle Expiratory Pressure (MEP) 48 and 104 cmH2O.The values of Six Minute Walk Test (6MWT) evaluation by BORG modified scale before and after PEP were 11 and 13 ( efforts), 2 and 3 (dyspnea), 0 and 1 (Leg Fatigue). The six-minute walking distance (6MWD) before and after PED were 170 and 190 m, equation reference with Nury’s formula showed percentage prediction before and after PEP respectively 29.2 and 32%, VO2Max; 4.96 and 6L, METs; 1.41 and 1.7. The St GeorgeRespiratory Questionnaire (SGRQ) before and after PEP were 20.6 and 49.5% (symptom), 86.6 and 45.1% (activity), 45.5 and 18.4% (impact) and 53.6 and 42% for total.Conclusion: Positive airway pressure exercise had beneficial effect on reducing air-trapping process in COPD and increasing the respiratory muscle strength for both expiratory and inspiratory muscle strength.Keywords: Chronic obstructive pulmonary disease, positive expiratory pressure device, respiratory muscle strength, six minutes walking distance